Development of singlet fission materials for improved solar cells - Wong, Magdalene Chia Ling (Nanyang Technological University, 2021)
Singlet fission is the process of the conversion of a singlet exciton to two triplets that provides the opportunity to improve the efficiency of the solar cells. It has become of interest to the researchers due to its potential to exceed the Shockley-Queisser limit for solar energy utilization. Many materials had been shown to exhibit singlet fission, ranging from small molecules to polymers.